Kegiatan observasi status gizi dan kesehatan pada penyandang disabilitas - Sari, Fitri Eka; Perdana, Agung Aji; Aryawati, Wayan (JOURNAL of Public Health Concerns, 2025)
Backghround: Meeting nutritional needs in children and adolescents is a key component of growth and development, particularly for persons with disabilities who have physical limitations. A 2023 UNICEF report revealed that children with disabilities in Indonesia face higher rates of malnutrition than children without disabilities. The prevalence of underweight and wasting is also higher in this group. Purpose: To describe the nutritional status of persons with disabilities aged 15–30 years at the Lampung Province Social and Disability Service Unit. Method: Observation activities to collect data by directly observing behavior or phenomena without intervention were conducted using a descriptive observational design at the Lampung Province Social and Disability Service Unit. Data collection was carried out through a survey with observation and interviews. The population in this study was all persons with disabilities aged 15–30 years in Bandar Lampung City, specifically those registered with the Uptd Disability Service Unit. Using a random sampling technique, 30 respondents were selected, consisting of individuals with hearing impairments, blindness, and physical disabilities. The instruments used have been designed to elicit relevant information regarding the experiences and needs of people with disabilities. Results: The majority of persons with disabilities at the Lampung Province Social and Disability Service Unit (UPTD) experience nutritional problems, primarily being underweight, likely due to low consumption of nutritious food and physical activity. Data shows that 69.9% of respondents are underweight, with low consumption of fruits, vegetables, protein (meat, fish, eggs, milk), and water. Seventy-three percent of respondents skip breakfast, with nearly half (46.7%) experiencing difficulty accessing nutritious food, lacking regular physical activity, and most only exercising once or twice a week. Common health problems include anemia, dizziness, fatigue, and digestive disorders. The majority (73.4%) of respondents have never received nutrition counseling, but consumption of supplemental vitamins remains uneven. Conclusion: This observation indicates that the majority of persons with disabilities at the Lampung Province Social and Disability Service Unit experience nutritional problems, with 69.9% of respondents categorized as underweight based on their body mass index (BMI). Furthermore, only 26.7% of respondents have received counseling on nutrition and healthy eating patterns. These findings indicate an urgent need for better nutritional interventions for people with disabilities, particularly in terms of education, food access, and nutritional status monitoring. Suggestion: Regular nutritional counseling programs, particularly on balanced nutrition and healthy eating patterns, are needed for people with disabilities in social institutions, using a friendly and easy-to-understand approach. Providing healthy food assistance by the government or social institutions is essential to ensure the availability and easy access of nutritious food for people with disabilities through subsidies or nutritional food assistance programs. As a follow-up program, health services are expected to conduct regular health monitoring, including nutritional and health status checks, for early detection of malnutrition and related diseases. Keywords: Disability health check-up; Nutritional needs; Nutritional status; People with disabilities Pendahuluan: Pemenuhan kebutuhan gizi pada anak dan remaja merupakan wujud utama dari proses pertumbuhan dan perkembangan. Khususnya bagi penyandang disabilitas yang memiliki kekurangan fisik. Laporan UNICEF tahun 2023 mengungkapkan bahwa anak penyandang disabilitas di indonesia menghadapi tingkat malnutrisi yang lebih tinggi dibandingkan anak tanpa disabilitas. Prevalensi underweight dan wasting juga lebih tinggi pada kelompok ini. Tujuan: Menggambarkan kondisi gizi penyandang disabilitas usia 15–30 tahun di Uptd Dinas Sosial Disabilitas Provinsi Lampung Metode: Kegiatan observasi untuk mengumpulkan data dengan mengamati langsung perilaku atau fenomena tanpa intervensi, yang dilakukan dengan disain deskriptif observasional yang dilaksanakan di Uptd Dinas Sosial Disabilitas Provinsi Lampung. Merupakan kegiatan pengambilan data melalui survei dengan observasi dan wawancara. Populasi dalam penelitian ini adalah seluruh penyandang disabilitas usia remaja hingga dewasa (15–30 tahun) yang berada di wilayah Kota Bandar Lampung, khususnya mereka yang terdaftar di Uptd Dinas Sosial Disabilitas. Dengan menggunakan teknik random sampling mendapatkan 30 orang sebagai responden yang terdiri dari individu dengan kondisi tuna rungu, tuna netra, dan tuna daksa. Instrumen yang digunakan telah dirancang untuk menggali informasi yang relevan terkait pengalaman dan kebutuhan penyandang disabilitas. Hasil: Mayoritas penyandang disabilitas di Uptd Dinas Sosial Disabilitas Provinsi Lampung mengalami masalah gizi, terutama kekurangan berat badan dan besar kemungkinan karena konsumsi makanan bergizi dan aktivitas fisik yang masih rendah. Data menunjukkan sebanyak 69.9% responden tergolong underweight, konsumsi buah, sayur, protein (daging, ikan, telur, susu), dan air putih masih rendah. Sebanyak 73.4% responden tidak sarapan setiap pagi dimana hampir setengah responden (46.7%) mengalami kesulitan mengakses makanan bergizi, aktivitas fisik rutin masih kurang, dan sebagian besar hanya olahraga 1-2 kali seminggu. Masalah kesehatan yang sering dialami antara lain anemia, pusing, mudah lelah, dan gangguan pencernaan. Sebagian besar (73.4%) responden belum pernah mendapat penyuluhan gizi tetapi konsumsi vitamin tambahan masih belum merata. Simpulan: Berdasarkan kegiatan observasi ini menunjukkan bahwa mayoritas penyandang disabilitas di Uptd Dinas Sosial Disabilitas Provinsi Lampung mengalami masalah gizi, dengan 69.9% responden berada dalam kategori underweight berdasarkan indeks massa tubuh (IMT). Di samping itu, hanya 26.7% responden yang pernah mendapatkan penyuluhan tentang gizi dan pola makan sehat. Temuan ini menunjukkan adanya kebutuhan mendesak akan intervensi gizi yang lebih baik bagi penyandang disabilitas, khususnya dalam hal edukasi, akses pangan, dan pemantauan status gizi. Saran: Perlunya dilakukan penyuluhan gizi dengan program yang berkala terutama mengenai gizi seimbang dan pola makan sehat bagi penyandang disabilitas di lembaga sosial, dengan pendekatan yang ramah dan mudah dipahami. Pemberian bantuan pangan sehat oleh pemerintah atau lembaga sosial sangat diperlukan untuk menjamin ketersediaan dan kemudahan akses bagi penyandang disabilitas terhadap makanan bergizi berupa subsidi atau program bantuan pangan bergizi. Sebagai program lanjutan, diharapkan pihak dinas kesehatan untuk melakukan pemantauan kesehatan secara berkala meliputi pemeriksaan status gizi dan kesehatan untuk mendeteksi dini masalah malnutrisi dan penyakit terkait.